Digitalisasi Mumifikasi Suku Dani Di Papua Menggunakan Teknologi Augmented Reality Berbasis Android - Anggara, Devi Willieam; Dahliyusmanto, Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bubula tribe or usually known as Dani tribe is a tribe in Papua, which has an unique culture named mummification culture of family’s member body. It is a rare culture which needs to be preserved. To introduce this culture, video with Augmented Reality (AR) technology is used. Markers is used in a AR technology to distinguish each video will be played. Using technology of Augmented Reality marker / marker based on tracking technology has several stages to develop. Such as, collecting data documentation video from about it’s history obtained from Technical Executing Unit (UPT) Museum Loka Budaya from Universitas Cendrawasih Papua, Indonesia. Cutting and compressing video size, designing marker and uploading marker, designing application interface, designing Augmented Reality technology into Android package format (APK). To design are next steps need to be done this application need some tools Unity 3D, Adobe Photoshop, Adobe Premier, Vuforia SDK, and Android SDK were needed. This research produces applications based on Android using Augmented Reality Technology (AR) as a media to display video. It can be done by scanning marker using Smartphone, so user can see video about Dani culture happily.Keywords : Augmented Reality, Marker Augmented Reality, Marker Based Tracking, Dani Tribe, Bubula Tribe